Effect of seasonal and environmental variation on yield and yield components of hybrid Maize - Islam, MK; Mahfuz, MS; Sarker, MAI; Ghosh, S; Ali, ASMY (International Journal of Agricultural Research, Innovation and Technology, 2015)
The experiment was conducted during kharif II in 2006 & 07, rabi in 2006-07 & 07-08 and kharif I in 2007 and 2008 at ARS, Burirhat, Rangpur in RCB design to understand the influence of season and location specific environment effect on growth and yield of hybrid maize and selected suitable variety(s). Four hybrid maize varieties V1=BARI hybrid Maize (BHM)-2, V2=BHM-3, V3= BHM-5 and V4= Pacific-984 (as check) were tested during kharif II in 2006 while seven varieties V1= BHM-2, V2= BHM-3, V3= BHM-5 and V4= Pacific-984, V5= Pacific-60, V6= Pacific-11 and V7= Prolin were during the other seasons except rabi, 07- 08, where variety Pacific-555 was used in V7 instead of Prolin. Seeds were sown on August 30 and August 11 for kharif II of 2006 and 2007, respectively, November 28 and 17 for rabi 2006-2007 and 2007-08 and March 08 and 12 for for kharif I 2007 and 2008. The crops were harvested on January 25, 2007 and January 12, 2008 in the two consecutive kharif II seasons; May 10 and April 29 in rabi 2006-07 and 2007-08, and July 01 and 05 in kharif I 2007 and 2008, respectively. Yield parameters were mostly varied significantly. The highest yield was obtained from BHM-5 (9.03 t ha-1), which was followed by Pacific-984 (8.89 t ha-1), BHM-3 (8.81 t ha-1) and BHM-2 (8.58 t ha-1) in kharif II, 2006 while in kharif II, 2007 the highest significant yield was noted in Pacific-984 (9.22 t ha-1). In rabi, 2006-07, significant highest grain yield was obtained from Pacific-60 (11.03 t ha-1), which was statistically identical with Prolin (10.20 t ha-1). The yield of Prolin was also statistically identical with Pacific-11 (10.01 t ha-1), BHM-5 (10.00 t ha-1), BHM-3 (9.92 t ha-1) and BHM-2 (9.51 t ha-1). Comparatively lower temperature during ear initiation (mean 29.6°C in rabi and 31°C in kharif II) and silking (mean 18.2°C in rabi and 20.2°C in kharif II) contributed much for higher trend of yield in rabi over kharif. In kharif I, 2007, the highest yield (9.55 t ha-1) was recorded from Pacific-60, which was identical to Pacific-984 (9.25 t ha-1), BHM-5 (9.11 t ha-1) and BHM-3 (8.89 t ha-1). All the BARI hybrid maize varieties were suitable to grown in kharif I, kharif II and rabi season although BHM-3, BHM-5, Pacific-60 and Pacific-984 were better in Kharif I and Pacific-60, BHM-5, Prolin and Pacific-555 were found better in Rabi season. DOI: http://dx.doi.org/10.3329/ijarit.v4i2.22635 Int. J. Agril. Res. Innov. & Tech. 4 (2): 1-5, December, 2014